2012
DOI: 10.21091/mppa.2012.3028
|View full text |Cite
|
Sign up to set email alerts
|

Core Stability: Implications for Dance Injuries

Abstract: Dancers experience a high incidence of injury due to the extreme physical demands of dancing. The majority of dance injuries are chronic in nature and occur in the lower extremities and low back. Researchers have indicated decreased core stability (CS) as a risk factor for these injuries. Although decreased CS is suggested to negatively affect lower extremity joint motion and lumbar control during activity, this relationship has not been extensively discussed in previous dance literature. Understanding the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…Previously conducted studies indicate that ballet, as a form of physical activity, causes low back pain 9 ) . Poor core stability is, perhaps, a predisposing factor for injuries to the lower limbs and lumbar spine in dancers, due to poor stabilization of the lumbo-pelvic complex 17 ) . Studies show that segmental muscle stabilization training as part of a core stability program decreased low back pain 18 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Previously conducted studies indicate that ballet, as a form of physical activity, causes low back pain 9 ) . Poor core stability is, perhaps, a predisposing factor for injuries to the lower limbs and lumbar spine in dancers, due to poor stabilization of the lumbo-pelvic complex 17 ) . Studies show that segmental muscle stabilization training as part of a core stability program decreased low back pain 18 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In the jumping practice of modern dance, if the rotation speed is too fast, the higher the speed at which the ankle is in contact with the ground, the higher the reaction force on the ankle, and the more likely it is to be injured (Christina et al, 2001). Moreover, if the dancer does not tighten the body or force incorrectly when jumping, it will be more likely to cause sports injuries (Rickman, 2012). For example, when we are practicing modern dance, we must accurately find the point of exertion and relaxation of remaining body parts, but this does not mean that the body is lax.…”
Section: Types Of Dance Injuries (Take Modern Dance As An Example)mentioning
confidence: 99%
“…Therefore, practicing core strength also plays a crucial role in preventing dance injuries. Because the core strength plays a role in the connection between the upper body and the lower body, the stability of the dancers can be effectively improved by training the core area strength (Rickman, 2012). For example, the practice of adding "center of gravity" in modern dance teaching, that is, the conversion of two legs during the process of travel, constantly changing the main leg and the power leg, or adding some rotation jumps, which not only requires the body's control ability, but also the dancer's responsiveness and flexibility are required.…”
Section: Ways To Prevent Dance Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that the scapula, shoulder muscles and lower extremity muscles must work coherently with the core muscles for controlled movements ( Hodges and Richardson, 1997a ; Hodges and Richardson, 1997b ). There are numerous studies conducted on the role of core stability to prevent especially back pains of athletes and injuries of lower extremities ( Abdelraouf and Abdel-Aziem, 2016 ; Hodges et al, 1997 ; Hölmich et al, 2010 ; Hübscher et al, 2010 ; Hungerford et al, 2003 ; Rickman et al, 2012 ). It has been shown in the literature that lower extremity injuries influence core stability measurements.…”
Section: Introductionmentioning
confidence: 99%